Utilization Of Tiktok as a Promotional Media for Tourist Destinations During The COVID-19 Pandemic - Endrianto, Gunawan; Gaffar, Vanessa; Pratiwi, Ilma Indriasri (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2023)
With the Covid-19 disaster, there must be a new strategy in promoting Dago Dreampark attractions, the right way to promote tourism objects is to use social media, this can be seen from the increase in downloading the Tiktok application which is currently trending. A strategy is needed so that the Dago Dreampark tourism business can still promote its tourist destinations by making good use of Tiktok in the era of the Covid-19 pandemic. This research method uses a qualitative approach with a case study method. In-depth data collection techniques used in the study were in-depth interviews and observation. The data analysis used is data collection, data reduction, data presentation and conclusion drawing.How Dago Dreampark utilizes Tiktok social media as a promotional medium by arranging several strategies such as using hashtags, collaborating, following current trends, clear descriptions and posting frequently. Not only that, Tiktok Dago Dreampark also takes advantage of the features provided to make the videos more interesting, such as music, voice changer filters, stickers and live. The role of Tiktoktun is increasingly felt when Dago Dreampark also creates loyal customers on the Tiktok platform, this can be seen in the habit of replying to comments in content on Tiktok, the source also stated that if there is a target in replying to a comment, which is between 2x24 hours of comments, comments on every Tiktok Dago Dreampark content must be replied.